1987
DOI: 10.1111/j.1600-065x.1987.tb00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the Neuroendocrine and Immune Systems: Common Hormones and Receptors

Abstract: The studies reviewed here support a molecular basis for bidirectional communication between the immune and neuroendocrine systems. The main findings can be summarized as follows: First, cells of the immune system can synthesize biologically active neuroendocrine peptide hormones. Second, immune cells also possess receptors for many of these peptides. Third, these same neuroendocrine hormones can influence immune function; and fourth, lymphokines can influence neuroendocrine tissues. Although recent studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0
7

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(97 citation statements)
references
References 66 publications
2
88
0
7
Order By: Relevance
“…In addition to the adrenal cortex (Voisey et al 2003), ACTH receptors are also found on adipocytes (Boston & Cone 1996), skin cells (Kapas et al 1998) and sympathetic ganglia (Nankova et al 1996). Furthermore, it has been proposed that ACTH can also participate in immunmodulation (Weigent & Blalock 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the adrenal cortex (Voisey et al 2003), ACTH receptors are also found on adipocytes (Boston & Cone 1996), skin cells (Kapas et al 1998) and sympathetic ganglia (Nankova et al 1996). Furthermore, it has been proposed that ACTH can also participate in immunmodulation (Weigent & Blalock 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous opiates exert immunostimulatory effects (3,4). Helper T cells produce endogenous opioids, and memory T cells within inflammatory tissue are capable of synthesizing and releasing β-endorphins (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that opioid receptors are expressed by cells of the immune system and that opioids modulate immune responses. In contrast to endogenous opiates that exert immunostimulatory effects (3,4), both the therapeutic and chronic use of morphine compromise the optimal function of the immune system (5). Opiate addicts are prone to infection.…”
Section: Introductionmentioning
confidence: 99%
“…The interrelationship of endocrine and immune systems is complex, but research into this area is progressing rapidly (245)(246)(247). The elucidation of this interaction between endocrine and immune systems is made more challenging with the addition of species diversity (e.g., shellfish, fish, birds).…”
Section: S=c\r-mentioning
confidence: 99%